Quality and reliability of security guards towards the perception of public in Kota Samarahan / Muhammad Ariff Mustafa Kamal - Mustafa Kamal, Muhammad Ariff (2015)
Security guard is known as a person that mainly provide protection to property, people and even asset. They are employed formally and usually uniformedly dressed as they act to protect property from inappropriate actions that are vast with the change of time. Their task mainly are to observe by performing patrols, monitoring the alarm system or closed circuit television (CCTV) for any for any sign of threats and disorder. If such thing happens, necessary actions, precautions and reports should be done to solve it. Some security guards have the authority to make an arrest, as long as the crime is within the are of their patrolled area. They are considered as law enforcement just like the police, but only within their perimeter.